Numerical Analysis of Transient Micro- elastohydrodynamic Lubrication of Cycloid Pinwheel - Jiang Yuanzhi; Wang Youqing (Jixie chuandong)
The full numerical solutions of transient micro- elastohydrodynamic lubrication of the cycloid pinwheel transmission are derived to take into account the variation of equivalent radii,entrainment velocity and load of meshing points by means of the multi- grid method,and the influence of single roughness peak and valley of meshed surfaces on this lubrication is studied. The results show that compared with smooth surface,the oil pressure changes significantly,yet it has little effect on the oil film thickness. Besides,there are different performances between roughness peak and valley obviously.